STRENGTHENING CHARACTER THROUGH THE 7 HABITS OF GREAT INDONESIAN CHILDREN. - Irma Suriani; Ismainun Lubis; Hotnida; Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Character building is a key focus of elementary education, aimed at developing students with noble character, independence, and responsibility. One approach is to implement the 7 Habits of Great Indonesian Children, encompassing religiousness, discipline, honesty, responsibility, caring, hard work, and love for the homeland. This study aims to analyze the role and implementation of the 7 Habits of Great Indonesian Children in strengthening the character of elementary school students. The method used was a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results indicate that consistent and integrated implementation of the 7 Habits of Great Indonesian Children in learning activities, daily routines, and school culture can improve students' attitudes of discipline, responsibility, honesty, social awareness, and religiosity. Furthermore, teacher involvement and support from the school environment are crucial factors in the success of character building. Therefore, the 7 Habits of Great Indonesian Children can be an effective strategy for building positive character in students sustainably.